Geometric and Electronic Structure of Isoxazole and Isothiazole Derivatives by PM3 and Density Functional Theory - Abdelmalek, O.; Belaidi, S.; Mellaoui, M.; Mazri, R. (Asian Journal of Chemistry, 2010)
The geometric and electronic structure of isoxazole and isothiazole and the effect of methyl group substitution in isoxazole and isothiazole derivatives have been studied by PM3 method and density functional theory. In the present work, the calculated values, namely net charges, bond length, dipole moments, ionization potentials, electron-affinities and heats of formation are reported and discussed in terms of the reactivity of isoxazole and isothiazole derivatives.